Gastric Plexiform Fibromyxoma Arising in the Cardia in an Adolescent Male: A Rare Tumor with an Unusual Location - Awrad Nasralla; Mufeed Alwabari; Osama Alsaif; Samir S. Amr (Case Reports in Surgery)
Plexiform fibromyxoma of the stomach, also known as plexiform angiomyxoid myofibroblastic tumor, is a rare benign gastric mesenchymal tumor, first described in 2007, which usually arises in the gastric antrum and affects adults. Few cases have been reported in children and adolescents. It can present with different clinical manifestations including abdominal pain, dyspepsia, hematemesis, and vomiting. Preoperatively, this tumor is usually diagnosed as gastrointestinal stromal tumor (GIST), and the correct diagnosis is made only after histopathological examination following surgical resection. Most cases were reported from East Asia (China, Japan, and Korea), North America, and Europe. We report herein a unique case of plexiform fibromyxoma, the first to be reported from the Middle East, arising in the cardia of the stomach in a 16-year-old adolescent male, with a brief review of the literature.